Among the truthers : a journey through America's growing conspiracist underground - Kay, Jonathan 1968- (Harper, 2011)
"America is awash with conspiracy theories, and the shared view of reality we once took for granted has been permanently shattered. Jonathan Kay uses the 9/11 Truth movement as a springboard to examine this fragmented national mindset"--Provided by publisher